Changes and drivers of freshwater mussel diversity and distribution in northern Borneo - Zieritz, Alexandra; Bogan, Arthur E.; Rahim, Khairil Adha; Jainih, Ronaldo Sousa Leonardo; Harun, Sahana; Abd Razak, Nabilah Fatin; Gallardo, Belinda; McGowan, Suzanne; Hassan, Ruhana; Lopes-Lima, Manuel (Elsevier, 2018)
Human activities are threatening Borneo's unique biodiversity, but little is known on the status of freshwater invertebrates. We assessed changes in diversity and distribution of freshwater mussels (Bivalvia: Unionida) in northern Borneo, and identified drivers of present distribution and threats. Past distribution data were collected from literature and museum resources. Present distribution data were collected from 21 river basins, and 47 water quality, climatic, landscape and human variables explored as potential predictors of species presence/absence. Species delimitations were identified by morphology and COI barcoding, and haplotype networks generated. Our data indicate that over the past 50 years, four of originally five native species have become very rare or possibly locally extirpated. Since these four species are endemic to Borneo, other Bornean river basins should urgently be surveyed to identify any remaining populations. In the same time span, the non-native Sinanodonta woodiana has become the most widespread freshwater mussel in northern Borneo. The fifth native species was identified as Rectidens sumatrensis and found in four Sarawakian river basins, thus contradicting previous assumptions of an endemic Bornean Rectidens species. Although a number of stable R. sumatrensis populations are retained across Sarawak, the species' strong spatial contraction in mainland Sundaland and apparent low tolerance to eutrophication suggest that it is vulnerable to further habitat alteration. Our results indicate that Borneo's (endemic) freshwater invertebrate biodiversity is declining rapidly. Comprehensive surveys targeting an array of invertebrate and vertebrate taxa are needed to identify Borneo's freshwater biodiversity hotspots, where conservation efforts should be concentrated.